Treatment regimens for pregnant women with falciparum malaria - Moore, Brioni; Salman, S.; Davis, T. (Expert Reviews Ltd., 2016)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Introduction: With increasing parasite drug resistance, the WHO has updated treatment recommendations for falciparum malaria including in pregnancy. This review assesses the evidence for choice of treatment for pregnant women. Areas covered: Relevant studies, primarily those published since 2010, were identified from reference databases and were used to identify secondary data sources. Expert commentary: WHO recommends use of intravenous artesunate for severe malaria, quinine-clindamycin for uncomplicated malaria in first trimester, and artemisinin combination therapy for uncomplicated malaria in second/third trimesters. Because fear of adverse outcomes has often excluded pregnant women from conventional drug development, available data for novel therapies are usually based on preclinical studies and cases of inadvertent exposure. Changes in antimalarial drug disposition in pregnancy have been observed but are yet to be translated into specific treatment recommendations. Such targeted regimens may become important as parasite resistance demands that drug exposure is optimized.